2004
DOI: 10.1097/01.mej.0000136696.49343.8f
|View full text |Cite
|
Sign up to set email alerts
|

Syncope in acute pulmonary embolism

Abstract: Syncope is not an uncommonly presenting manifestation of acute PE. Patients with acute PE and syncope have similar characteristics to those without syncope. Syncope does not seem to determine a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 6 publications
2
22
1
11
Order By: Relevance
“…10 -33 Three studies were excluded 30 -32 because they appeared to report on the same patients included in other analyzed studies. 16 -23 In 6 studies, 16,18,23,24,29,33 the numbers of patients who had died or had experienced an adverse outcome event were not reported. For 5 of these studies, the numbers of patients who had died or had experienced an adverse outcome event were obtained by contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 -33 Three studies were excluded 30 -32 because they appeared to report on the same patients included in other analyzed studies. 16 -23 In 6 studies, 16,18,23,24,29,33 the numbers of patients who had died or had experienced an adverse outcome event were not reported. For 5 of these studies, the numbers of patients who had died or had experienced an adverse outcome event were obtained by contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
“…16,18,23,24,29 One of these studies was excluded after the authors were contacted because data were confirmed to be unavailable. 33 …”
Section: Resultsmentioning
confidence: 99%
“…Senkop; bizim vakalarda da olduğu gibi yapılan bir çalışmada da pulmoner embolisi olan bir vakanın acile tek ve ilk başvuru semptomu olabilir [9]. Senkop PE'nin gözardı edilebilecek bir belirtisi olduğu için acil servise senkop ile başvuran hastaların ayırıcı tanısında PE mutlaka düşünülmelidir [10,11]. Demircan ve ark.…”
Section: Discussionunclassified
“…La prevalencia de síncope como manifestación inicial de la TEP fue de un 22% en nuestra experiencia, superior a la de otras series de la bibliografía 18 pero similar a la de Toda et al 19 . Muy probablemente, existe en nuestro medio un grado de sospecha alto de diagnóstico de TEP en todo paciente que presenta un episodio sincopal sin causa cardiológica obvia; por el contrario, es probable que en las series clásicas la TEP sólo se sospechara en los casos que mantenían inestabilidad hemodinámica a su llegada al centro hospitalario.…”
Section: Discussionunclassified